Permanent anastomotic access hepatic-jejunal - Corradi, Daniel; Bounous, Mario; Carrerou, Luis A (Cirugía del Uruguay, 1990)
The authors present two cases of hepatico-jejunal derivations on defunctionalized Roux-en-Y loop, with technical variations that make possible easy and iterative access to the anastomosis and the biliar tree for the treatment of these derivations· evolutionary complications